The rose [videorecording (DVD)] - Midler, Bette; Bates, Alan, 1934-2003; Forrest, Frederic; Keith, David, 1954-; Stanton, Harry Dean, 1926-2017 (Criterion collection, 2015)
Rose is one of the biggest rock stars on the planet. Her life of constant sex, drugs and rock and roll, along with constant touring, prove to be too much to handle. Nominated for four Academy Awards.